2020
DOI: 10.1101/2020.06.04.135251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GermlineAPOBEC3Bdeletion in Asian women increases somatic hypermutation in breast cancer that is associated with Her2 subtype,PIK3CAmutations, immune activation, and increased survival

Abstract: A 30-kb deletion that eliminates the coding region of APOBEC3B (A3B) is >5 times more common in women of Asian compared to European descent. This polymorphism creates a chimera with the APOBEC3A (A3A) coding region and A3B 3’UTR, and is associated with an increased risk for breast cancer in Asian women. Here, we explored the relationship between the A3B deletion polymorphism with tumour characteristics in Asian women. Using whole exome and whole transcriptome sequencing data of 527 breast tumours, we report… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This locus was shown to be significantly associated with breast cancer risk in different populations including those of Chinese, Iranian, and European ancestries [ 18 , 47 , 48 ]. It was demonstrated also that deletion in the APOBEC3 loci disrupting APOBEC3A and APOBEC3B genes lead to the decreased expression of the corresponding genes [ 66 , 67 ]. Moreover, the association between GSTT1 gene deletion and breast cancer risk has been widely studied and it was demonstrated that GSTT1 null genotype is associated with increased breast cancer risk [ 68 ] and also with significant downregulation of GSTT1 gene resulting in loss of protein expression [ 69 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…This locus was shown to be significantly associated with breast cancer risk in different populations including those of Chinese, Iranian, and European ancestries [ 18 , 47 , 48 ]. It was demonstrated also that deletion in the APOBEC3 loci disrupting APOBEC3A and APOBEC3B genes lead to the decreased expression of the corresponding genes [ 66 , 67 ]. Moreover, the association between GSTT1 gene deletion and breast cancer risk has been widely studied and it was demonstrated that GSTT1 null genotype is associated with increased breast cancer risk [ 68 ] and also with significant downregulation of GSTT1 gene resulting in loss of protein expression [ 69 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In carriers of the polymorphism, a high TMB is associated with increased immune infiltration and enrichment of an adaptive immune response signature 11,12,35,36 . In addition, in other cancer types such as lung cancer and cervical cancer, APOBEC hypermutation has been associated with these characteristics and improved response to immune checkpoint inhibition, even in samples that did not pass the ‘high TMB’ threshold of 10 mutations/Mb 10‐12,38‐41 . This suggests that it is possible that APOBEC hypermutation, may in itself be predictive of response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 35 , 36 In addition, in other cancer types such as lung cancer and cervical cancer, APOBEC hypermutation has been associated with these characteristics and improved response to immune checkpoint inhibition, even in samples that did not pass the ‘high TMB’ threshold of 10 mutations/Mb. 10 , 11 , 12 , 38 , 39 , 40 , 41 This suggests that it is possible that APOBEC hypermutation, may in itself be predictive of response to immunotherapy. Therefore, an APOBEC enrichment score, combined with a TMB estimate, may provide additional clinical utility compared to a TMB estimate alone.…”
Section: Discussionmentioning
confidence: 99%
“…In carriers of the polymorphism, a high TMB is associated with increased immune infiltration and enrichment of an adaptive immune response signature 13,14,39,40 . In addition, in other cancer types such as lung cancer and cervical cancer, APOBEC hypermutation has been associated with these characteristics and improved response to immune checkpoint inhibition, even in samples that did not pass the "high TMB" threshold of 10 mutations/Mb [12][13][14][42][43][44][45] . This suggests that it is possible that APOBEC hypermutation, may in itself be predictive of response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%